The Use of AuRIX«100 Resin for the Selective Recovery of Gold and Silver From Copper, Gold and Silver Solutions - T Hughes; J Abols (The Australasian Institute of Mining and Metallurgy, 2005)
The selective recovery of gold and silver from solutions containing other metals, such as copper, is possible using AuRIX«100 resin in conjunction with the Gekko Resin Column. Selectivity is driven by controlling the solution pH, which enables activities such as loading copper, gold and silver and then selectively stripping copper before gold and silver. Alternatively gold and silver can be loaded and the copper left in solution. The selective loading of gold while reducing the silver loading has also been demonstrated, opening the possibility of producing high grade gold dorT from high grade silver pregnant leach solutions. This paper reviews the AuRIX«100 resin and Gekko Resin Column Technologies, discusses the uses of AuRIX«100 in the recovery of gold and silver and the chemistry relating to several projects for which AuRIX«100 is being tested.